Estimation of the effectiveness of diagnostic control systems - Kutin, V. M.; Iliukhin, M. O.; Kutina, M. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
It is suggested to use entropy as a measure of estimation of the diagnostic control system efficiency. The analytical dependence for determination of the object for diagnosis at any moment of time and effectiveness of the diagnostic control system is determined.